MODEL PEMBELAJARAN KOLABORATIF DAN ASESMEN AUTENTIK PADA PEMBELAJARAN BAHASA INGGRIS - Agustini, Lilik Indriasasi (Jurnal Evaluasi Pendidikan, 2016)
The purpose of this research is to find out the effect of collaborative instructional model and authentic assessment towards student’s English achievement. The method used was an experimental method. While the design used was the factorial 2x2 design. Research hypotheses were tested by using analysis of variance (ANOVA). This research concluded that STAD cooperative learning model can be paired with the authentic assessment of portfolio and project types in English learning. More over the Learning Model in English Learning must consider the use of alternative form of assessment.